2017
DOI: 10.13057/cellbioldev/v010102
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductivity for seed vigor test in sorghum (Sorghum bicolor)

Abstract: Abstract. Fatonah K, Suliansyah I, Rozen N. 2017. Electrical conductivity for seed vigor test in sorghum (Sorghum bicolor). Cell Biol Dev 1: 6-12. The objectives of this study were to obtain electrical conductivity test method for seed vigor test in sorghum, to recognize relationship between electrical conductivity test and potassium leakage, and to recognize relationship between electrical conductivity test and other variable on seed vigor. This study have two step experiments. The objective of Experiment I w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…Many research works have been conducted to construct potential rapid and non-destructive methods to measure seed vigor. Four non-destructive approaches with different techniques or principles, i.e., nuclear magnetic resonance spectroscopy [7], X-ray [8,9], laser speckle technique [10] and the measuring technology of seed conductivity [11] were investigated, however, they have not been widely used because of the low efficiency and complicated operation. Fortunately, recent studies show that molecular spectroscopic techniques, such as point-based and image-based hyperspectral techniques, have great potentials in the detection of seed ingredients with the advantages of high detection speed, non-destructive nature and low cost [12].…”
Section: Introductionmentioning
confidence: 99%
“…Many research works have been conducted to construct potential rapid and non-destructive methods to measure seed vigor. Four non-destructive approaches with different techniques or principles, i.e., nuclear magnetic resonance spectroscopy [7], X-ray [8,9], laser speckle technique [10] and the measuring technology of seed conductivity [11] were investigated, however, they have not been widely used because of the low efficiency and complicated operation. Fortunately, recent studies show that molecular spectroscopic techniques, such as point-based and image-based hyperspectral techniques, have great potentials in the detection of seed ingredients with the advantages of high detection speed, non-destructive nature and low cost [12].…”
Section: Introductionmentioning
confidence: 99%
“…A decrease in germination and seed growth capacity follows the electrical conductivity increment, as has been proven in R. apiulata propagules (Rohandi and Widyani, 2010), sorghum seeds (Fatonah and Rozen 2017), soybean seeds (Noviana et al 2017) and A. mangium (Pujiastuti and Sudrajat 2017). In contrast to this study, the electrical conductivity increment was not followed by a decrease in seed germination or vice versa.…”
Section: Discussionmentioning
confidence: 68%
“…From our study, it is interesting to note that the EC value is strongly associated with seed quality, suggesting that the EC value is an efficient indicator for seed vigor of sweet corn. is parameter was also suitable for sweet corn [36,37] and other crops including pea [38], sorghum [39], and safflower [40]. However, Zhao et al [36] reported that the EC test was only reliable to estimate the seed vigor of sweet corn with the se gene.…”
Section: Changes Of Seed Germination and Vigor During Seedmentioning
confidence: 99%